Barriers Affecting Contribution of Developing Countries Social Scientists in ISI Indexed Journals - Shirazi, Ali (Information Management and Business Review, 2011)
The decades leading to the third millennium was marked with concerted efforts by governments to raise their knowledge generation and contribution profile in the community of nations. Thus, all kinds of financial and promotional incentives have been offered to academics and researchers to publish papers in international journals, particularly ISI journals. It is argued that quantity and quality of articles published in ISI journals is an indication of scientific capabilities of a country and a yardstick for assessing its development. This research study aims to identify barriers that academics face in publishing papers in ISI social/humanity science journals. A questionnaire based on extensive literature review and a series of unstructured interviews was developed and tested. A stratified sampling method was used to collect data from academics of four social/humanity science faculties of a provincial university in the northwest of Iran. The findings revealed that respondent’s perceived lack of proficiency in a foreign language, poor information technology infrastructure and inadequate access to international scientific databases and uncontrollable factors related to the nature of social science disciplines and political climate as the major barriers that prevent or de-motivate them to publish in ISI journals. The research findings were discussed and concluded, and recommendations were made to reduce or remove barriers to publishing in ISI journals.